Working towards diversity with a postmigrant perspective: how to examine representation of ethnic minorities in cultural institutions. Issue 2 (21st August 2017) - Vitting-Seerup, Sabrina
ABSTRACT: This article presents ways for researchers and cultural workers to find and examine versions of representation in cultural institutions through a postmigrant perspective. The starting point is Denmark—a European nation state with, like many others, a diverse composition of citizens. This diversity is, however, poorly represented in Danish cultural institutions and the problem is difficult for many cultural workers to discuss due to the hesitation large segments of the Danish population feel about using terms associated with race and religion. Since much of the research regarding representation is strictly critical in its approach, it is also challenging to find the proper tools and language to discuss and correct the current skewed situation. This article is intended to provide balance in representation, first by presenting a model of four levels for potential positioning of diverse representation in cultural institutions and, secondly, by addressing the problems of access and depiction in regards to representation.